Legal Reasoning for the National Sharia Council – Indonesian Ulema Council Fatwa on Guarantees, Liquidity, and Sharia Compliance of Gold Rahn in Islamic Financial Institutions - Muhammad Ma’rur; Bustanul Arifin (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2026)
Background. The increasing use of gold-based rahn (Islamic pawn) in Islamic Financial Institutions (IFIs) has positioned it as a prominent short-term liquidity instrument. However, its rapid expansion raises concerns regarding substantive Sharia compliance, particularly in relation to the implementation of National Sharia Council – Indonesian Ulema Council (DSN-MUI) fatwas and the proper structuring of contracts. Aim. This study aims to analyze the conformity of gold rahn practices with the principles of fiqh muʿāmalah and DSN-MUI fatwas, as well as to examine their implications for liquidity stability and risk mitigation within IFIs. Methods. The research employs a library research design using a normative-juridical approach combined with legal reasoning analysis. Relevant classical fiqh literature, contemporary Sharia regulations, and DSN-MUI fatwas are examined to assess the legal structure and operational mechanisms of gold rahn practices. Results. The findings indicate that normatively, gold rahn practices fulfill the essential pillars and conditions of the contract. Nevertheless, at the implementation level, potential deviations are identified in the determination of ujrah (service fees) and contractual transparency. Strengthened Sharia compliance plays a strategic role in enhancing risk mitigation mechanisms and maintaining customer trust, thereby contributing to the liquidity stability of IFIs.